Transmissible Spongiform Encephalopathies & Prion Proteins: A Systematic Review - Poddar, Anirban; Kundu, T. N.; Ray, Manaly Sinha; Maji, Rituparna (Hasanuddin University, 2023)
Prion proteins (PrPc) have been implicated as the causative agent of “Transmissible Spongiform Encephalopathies” (TSE). Apart from this devilish role, prions also have a bright facet of their own and their identity holds much more than just being a pathogenic entity. Role of prions as scaffolding proteins for ligand binding and signal transduction has been reported by several researchers. Role of prions in nerve impulse transmission at neuronal junctions, glyapse and gap junctions have been reported. Prion mediated regulation of calcium ion flux and redox status in turn regulates many major cellular functions. In this review we have focussed mainly on the physiological aspects of prion function apart from its pathological role in TSE. Role of prions in mediation of neuropathic pain, neuroinflammatory diseases and chronic headache has been reported by few researchers. In this review we have tried to correlate such effects of prions and also discuss various therapeutic targets for various diseases influenced by prions.